2012
DOI: 10.1186/1749-8546-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Prescription profile of Chinese herbal products containing coumestrol, genestein, and/or daidzein among female users: an analysis of national health insurance data in Taiwan between 1997 and 2007

Abstract: BackgroundSome Chinese herbs contain several kinds of phytoestrogens, and these herbs are commonly prescribed in Taiwan. Phytoestrogens may influence the effects of estrogen in females, although their activities are weak. This study aims to identify the risk and analyze the prescription profile of commonly used phytoestrogenic herbs in Taiwan.MethodsThe study analyzed women who had been prescribed phytoestrogenic herbs including coumestrol, genistein and/or daidzein between 1997 and 2007 in a fixed cohort take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…The above-mentioned compounds have also been proved to have a preventive or therapeutic effect on some diseases. Wu et al [18] showed that coumestrol exerts a chemotherapeutic effect on gynecological tumors through the PI3K and ERK1/2-MAPK pathways, and is a potential novel treatment that prevents against ovarian cancer development. Zhao et al [19] found that psoralen has the estrogen-like effect through cell experiments, but its affinity for ER is weaker than that of estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned compounds have also been proved to have a preventive or therapeutic effect on some diseases. Wu et al [18] showed that coumestrol exerts a chemotherapeutic effect on gynecological tumors through the PI3K and ERK1/2-MAPK pathways, and is a potential novel treatment that prevents against ovarian cancer development. Zhao et al [19] found that psoralen has the estrogen-like effect through cell experiments, but its affinity for ER is weaker than that of estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in Japan found that it did not significantly prevent the progression of cold symptoms (20). A point worth noting is that a study in Taiwan found that women who take GGT for relief of respiratory discomfort are unexpectedly exposed to phytoestrogen generated by Ge gen (21). Nearly 5% of female users of Chinese medicines consumed cumulative doses of Ge gen above 60 g (21).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…A point worth noting is that a study in Taiwan found that women who take GGT for relief of respiratory discomfort are unexpectedly exposed to phytoestrogen generated by Ge gen (21). Nearly 5% of female users of Chinese medicines consumed cumulative doses of Ge gen above 60 g (21). Since little is known about the action of phytoestrogenic herbs in female patients, physicians need to be aware of threats to the female endocrine system when prescribing such herbs.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…However, the phytoestrogens of Gegen (coumestrol, genistein, and daidzein) may have potential interactions with the endocrine system, and therefore special attention should be drawn to the herbal formulae containing Gegen, especially the prescriptions for female patients at reproductive age suffering from respiratory diseases [ 117 ]. Also, a herb-drug interaction study pointed out that isoflavones and their glycosides and other polyphenols of Gegen might be transformed into conjugated metabolites in SD rats to compete with methotrexate (a drug for cancer treatment and may cause very serious, life-threatening side effects) to delay the elimination of methotrexate, increasing its life-threatening toxicity [ 118 ].…”
Section: Studies Of Single Herbsmentioning
confidence: 99%